Family and Individual Factors in the at Risk Population - Masoud Mohammadi; Ali Reza Jazayeri; Amir Hossein Rafiei; Bahram Jokar; Abbas Pourshahbaz (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: Based on the past studies in the filed of substance abuse, this study is to compare at risk populations regarding to familial and individual factors. Materials & Methods: this study have been done on 716 at risk individual in 11 city of Fars province. Research tools includes:1- locus of control inventory 2- Attachment styles scale 3- Parental Bonding Instrument 4- Resilience Scale 5- Coping Skills Inventory 6- Self Esteem scale. Results: there was a significant difference between normal and user and abuser groups. In resiliency, self esteem, problem oriented coping skills, caring and secure attachment normal group had a higher scores. But in ambivalent attachment style, external locus of control, emotion oriented and less benefit coping skills, normal group had a lower scores. In resiliency, ambivalent attachment style, problem oriented coping skills, and less benefit coping skills there was significant differences between user and abuser groups. But this was not true for caring, overprotection, secure attachment, locus of control, self esteem, and emotion oriented coping skills. Conclusion: according to these finding and in order to development and promotion of resiliency for substance abuse, preventive intervention should focus on educating parents and caregivers in the field of caring, enough protection, developing secure attachment, strategies for development and maintenance of self esteem, internal locus of control, and use of problem oriented coping skills. Psychological interventions also can use these finding in order to focus their therapy goals.